(untitled) (Journal of the College of Basic Education, 2022)
The purpose of this research is to identify the general features of the city of Anvil, its civilizational data, and its political conditions during the era of the Mahanea Emirate, within the phenomenon of the independent Arab Islamic Emirates, which returned the last stages of direct Arab Islamic rule of Sindh after the administration of the province was added to Khorasan. The research attempted to reach the most prominent results of the transformation of Sndan into a small emirate adjacent to the country of India and the Abbasid Caliphate, while trying to maintain the legitimate mandate of governance from the contemporary Abbasid caliphs of the emirate, and the advantage of that experience of historical events and circumstances .